Development of an Android Based Home Automation System - Okomba, Nnamdi; ESAN, Adebimpe; OMODUNBI, Bolaji; SOBOWALE, Adedayo; ADANIGBO, Opeyemi (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
As automation technology keeps advancing, the future of modern homes is continually changing from manual system into automatic ones that include remote control process. A Conventional means of accessing home electronic appliances is rigid and demands user presence to attend to different locations of such appliances before they can be used, this can be stressful for the elderly, the cripples, and provides limited ease of operation for everyone. The need for wireless communication function of the home appliances becomes very important in order to increase the flexibility of accessing them remotely by a user. Accessing and control of electronic devices and appliances used at home through a remote process is the main purpose for the development of a portable home automation system using app that is based on an android phone. ESP8266 microcontroller was interfaced to a servo motor that controls door movement and also to an AC bulb through a relay at the signal receiver end of the system. An MIT application inventor platform was used to build a mobile app on an android phone at the signal transmitter end of the system; this enables the transmission of on and off signals to the receiver end through Wi-Fi connection to access the connected loads (door and lamp). The hardware and software architecture of the developed home automation system was described in this paper. Implementation of a prototype of the designed system was carried out after which the system was tested on hardware as it yields expected results.